Identification of Metal Ligands in the Clostridium histolyticum ColH Collagenase - Jung, Chang-Min (American Society for Microbiology, 1999)
A Clostridium histolyticum 116-kDa collagenase has an H(415)EXXH motif but not the third zinc ligand, as found in already characterized zinc metalloproteinases. To identify its catalytic site, we mutated the codons corresponding to the three conserved residues in the motif to other amino acid residues. The mutation affecting His(415) or His(419) abolished catalytic activity and zinc binding, while that affecting Glu(416) did the former but not the latter. These results suggest that the motif forms the catalytic site. We also mutated the codons corresponding to other amino acid residues that are likely zinc ligands. The mutation affecting Glu(447) decreased markedly both the enzymatic activity and the zinc content, while that affecting Glu(446) or Glu(451) had smaller effects on activity and zinc binding. These mutations caused a decrease in k(cat) but no significant change in K(m). These results are consistent with the hypothesis that Glu(447) is the third zinc ligand. The spacing of the three zinc ligands is the same in all known clostridial collagenases but not in other known gluzincins, indicating that they form a new gluzincin subfamily. The effects of mutations affecting Glu(446) and Glu(451) suggest that the two residues are also involved in catalysis, possibly through an interaction with the two zinc-binding histidine residues.